Application of The Rapid Entire Body Assessment (REBA) Method to Improve Work Safety in The Automotive Spare Parts Industry - Fathurohman, Muhamad; Sukapto, Paulus; Susanto, Sani (Jurnal Improsci, 2024)
This industry consists of companies engaged in metal processing and workmanship. Companies often receive complaints from employees concerning pain or discomfort in their bodies, causing diseases such as low back pain and myalgia. The risk of accidents occurring at work is inseparable from the work done. Work-related accidents can occur due to several factors, including unsafe action. One cause of unsafe actions can be found in various unsafe work postures that workers assume. Therefore, the purpose of this study is to evaluate the posture of these workers so that it can improve their safety and health. This research was conducted by identifying occupational risks workers face and examining work performed in stamping products. The production section consists of six stations: material handling, stamping, welding, hemming, painting, and packing. The work risks run by workers have been identified using the Nordic Body Map (NBM) questionnaire and interview methods. As for the identification of the type of work carried out by evaluating work postures, the Rapid Entire Body Assessment (REBA) method has been employed. The risk level of accidents is also used for the selection of activities to be improved to minimize the level of injury risk caused by work postures that have been assumed, and in order to improve the safety and health of the workers. Improvements made are in engineering, such as manufacturing of assistive devices, and management engineering, such as providing directions that can improve the specific work posture used. Calculations are based on simulations performed with tools conducted with suggested postures by evaluation using the REBA method. Based on the results of REBA calculations, the resulting risk is lower than the one caused by the previously assumed posture, namely medium and low.